Nutrition education in U.S. medical schools - National Research Council; Division on Earth and Life Studies; Commission on Life Sciences; Food and Nutrition Board; Committee on Nutrition in Medical Education (National Academy Press, 1985)
This book examines the practice of nutrition instruction as part of medical education, reports on a study of its practice, describes nutrition education in the past, argues for greater attention to the topic and describes current practice. Chapter 1 (an executive summary) highlights the major findings and recommendations resulting from the study of nutrition education. chapter 2 discusses the forces that have shaped the role of nutrition in the medical curriculum during this century. Chapter 3 reviews knowledge implicating nutrition as one of the etiological factors contributing to many forms of chronic and degenerative disease. Chapter 4 contains summaries of previous conferences, congressional hearings, and surveys that have examined this subject as well as reviews of other relevant reports. An outline of core concepts and a basic body of nutrition knowledge that all graduating medical students should acquire during their medical training are presented in chapter 5. Chapter 6 summarizes the findings based on all the data analyzed and presents strategies for effectively incorporating nutrition into the medical school curriculum. Chapters 2, 3, and 4 include extensive references. Also included are an index and, in appendixes, survey forms, technical information on the study, testimony of the American Medical Student Association, and a report on the nutrition science content of National Board examinations. (JB)